High-order harmonic generation enhanced by XUV light: erratum - Buth, Christian (Optics letters, 2023)
This erratum to our Letter [Opt. Lett.36, 3530 (2011)10.1364/OL.36.003530] corrects minor errors. The computations are expected to be minorly influenced, and the conclusions of the original letter are not affected.
Online veröffentlicht am 6. Januar 2023
Gesehen am 12.12.2023